Explaining the Impact of Perceived Career Growth and Organisational Justice on Intention to Stay - Mehmood, Sultan Adal; Nadarajah, Devika; Akhtar, Muhammad Saood (International Journal of Economics, Business, and Entrepreneurship, 2018)
This study aimed to investigate intention to stay among officers in the City Traffic Police Lahore in relation to their perceptions of organisational justice and career growth. Using a quantitative research approach, a sample of 224 traffic wardens working in 30 sectors in the city of Lahore were selected through stratified random sampling. Data were gathered using a questionnaire containing Likert-type scales relating to all variable of interest. Apart from procedural justice and professional ability development, all dimensions of organisational justice and perceived career growth were found to significantly influence traffic officers’ intention to stay. Moreover, promotional speed emerged as the strongest predictor of the intent to stay. The findings of this study may guide police authorities in dealing with issues on turnover by initiating policies which can strengthen employee retention intention. Additionally, it provides empirical insights on the contributing factors of high turnover in the City Traffic Police Lahore. This paper enhances understanding of turnover issues by investigating retention intention of traffic police officers in an Eastern culture. Specifically, this research contributes to literature by examining the predictive role of organisational inducement factors (organisational justice and career growth) on attitude (intention to stay). Additionally, both the exogenous constructs of interest are used at the dimensional levels.